2014
DOI: 10.1152/japplphysiol.00605.2013
|View full text |Cite
|
Sign up to set email alerts
|

Human adaptation to the hypoxia of high altitude: the Tibetan paradigm from the pregenomic to the postgenomic era

Abstract: The Tibetan Plateau is one of the highest regions on Earth. Tibetan highlanders are adapted to life and reproduction in a hypoxic environment and possess a suite of distinctive physiological traits. Recent studies have identified genomic loci that have undergone natural selection in Tibetans. Two of these loci, EGLN1 and EPAS1, encode major components of the hypoxia-inducible factor transcriptional system, which has a central role in oxygen sensing and coordinating an organism's response to hypoxia, as evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 96 publications
(138 reference statements)
4
92
1
3
Order By: Relevance
“…Moreover, mounting evidence suggests that the observed physiological adaptations are dependent on the HIF pathway [4042]. In our study, 16 DEGs were also enriched as members of the HIF pathway (Fig 3 and S2 Table).…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, mounting evidence suggests that the observed physiological adaptations are dependent on the HIF pathway [4042]. In our study, 16 DEGs were also enriched as members of the HIF pathway (Fig 3 and S2 Table).…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, studies have shown evidence of natural selection among HIF pathway and hypoxia-related genes (Table 3B). Two genes are particularly noteworthy because of the consistency with which they have been observed in these studies (Simonson et al 2012;Petousi and Robbins 2014). One is HIF2A, which shows evidence of positive directional selection (selection for advantageous mutations that increase fitness of carriers) in all of these genome-wide analyses (Beall et al 2010;Bigham et al 2010;Simonson et al 2010;Yi et al 2010;Peng et al 2011a;Wang et al 2011;Xu et al 2011), and both HIF2A SNP genotypes and haplotypes significantly associate with low hemoglobin concentration in Tibetans (Beall et al 2010;Yi et al 2010).…”
Section: Tibetan Adaptation To High Altitude and Genetic Analysesmentioning
confidence: 59%
“…For example, the noncoding EPAS1 variants that are present at an elevated frequency among Tibetan highlanders are associated with a reduced hemoglobin concentration (18,172,216), which appears to stem from a blunted erythropoietic response to hypoxia (15-17, 19, 147, 210). There are good reasons to think that this blunted response may be physiologically beneficial under conditions of chronic hypoxia at high altitude (147,148,177,184,199), but that does not mean that hemoglobin concentration was necessarily the trait under direct selection. The reduced hemoglobin concentration may represent a second-order consequence of upstream modifications in O 2 chemosensitivity.…”
Section: Insights Into the Genetic And Mechanistic Basis Of Physiologmentioning
confidence: 99%